Natural ventilation in housing design / Hafidi Abu Hassan - Abu Hassan, Hafidi (2001)
Many new housing in Malaysia now are based on the western context and experience, often fail although attempts are made to adapt it to local condition. They are ill-suited to local climate and create social setting and living environments which are alienating and do not fit the local culture. For a tropical country like Malaysia, natural ventilation is most sensible form of ventilation system. It has the advantage of being easy to be constructed and cheaper to maintain compared with the mechanical system. Natural ventilation can easily be achieved by the provision of specific apertures in the building fabric, such as open able windows and ventilator ducts, which can be control by the building’s occupants. This dissertation will focus on designing the natural ventilation system by looking on its element and factors are got to consider in designing the natural ventilation system for residential house. The traditional Malay house and modern housing design are taken as a case study.